No evidence of endometriosis within serous and mucinous tumors of the ovary - Tadashi, Terada (e-Century Publishing Corporation, 2012)
Ovarian endometriosis can transform into malignant tumors. The author retrospectively examined HE slides of 112 serous tumors and 75 mucinous tumors for the existence of ovarian endometriosis. When endometriosis is present within the tumors, the term “endometriosis-derived tumor” was applied. When endometriosis is recognized adjacent to the tumor, the term “endometriosis-associated tumor” was used. Of the 112 serous tumors (46 benign, 18 borderline, and 50 malignant), 4 (3.5%) (2 benign and 2 malignant) were endometriosis-associated tumors. None was endometriosis-derived tumor. Of the 75 mucinous tumors (30 benign, 26 borderline, and 19 malignant), 4 (5%) (1 borderline and 3 benign) were endometriosis-associated tumors. No tumors showed endometriosis-derived tumors. The data suggest that endometriosis does not transform into serous and mucous tumors. The author felt the limitation of retrospective survey, because the limited numbers of slides (5 to 15) were obtained from each tumor. The author also felt that endometriosis can be difficult to discern because of degenerative changes and other similar lesions such as fallopian tube, fimbria, inclusion cysts, rete ovarii, paraovarian cyst, and Müllerian ducts remnants. Prospective study using whole ovarian examination is required.